Enhancing Personality Assessment in the Selection Context: A Study Protocol on Alternative Measures and an Extended Bandwidth of Criteria - Schröder, Valerie S.; Heimann, Anna Luca; Ingold, Pia V.; Kleinmann, Martin (Frontiers in Psychology, 2021)
Personality traits describe dispositions influencing individuals’ behavior and performance at work. However, in the context of personnel selection, the use of personality measures has continuously been questioned. To date, research in selection settings has focused uniquely on predicting task performance, missing the opportunity to exploit the potential of personality traits to predict non-task performance. Further, personality is often measured with self-report inventories, which are susceptible to self-distortion. Addressing these gaps, the planned study seeks to design new personality measures to be used in the selection context to predict a wide range of performance criteria. Specifically, we will develop a situational judgment test and a behavior description interview, both assessing Big Five personality traits and Honesty-Humility to systematically compare these new measures with traditional self-report inventories regarding their criterion-related validity to predict four performance criteria: task performance, adaptive performance, organizational citizenship behavior, and counterproductive work behavior. Data will be collected in a simulated selection procedure. Based on power analyses, we aim for 200 employed study participants, who will allow us to contact their supervisors to gather criterion data. The results of this study will shed light on the suitability of different personality measures (i.e., situational judgment tests and behavior description interviews) to predict an expanded range of performance criteria.